Envenomations by Bothrops and Crotalus snakes induce the release of mitochondrial alarmins. - Irene Zornetta; Paola Caccin; Julián Fernandez; Bruno Lomonte; José María Gutierrez; Cesare Montecucco (Public Library of Science (PLoS), 2012)
Skeletal muscle necrosis is a common manifestation of viperid snakebite envenomations. Venoms from snakes of the genus Bothrops, such as that of B. asper, induce muscle tissue damage at the site of venom injection, provoking severe local pathology which often results in permanent sequelae. In contrast, the venom of the South American rattlesnake Crotalus durissus terrificus, induces a clinical picture of systemic myotoxicity, i.e., rhabdomyolysis, together with neurotoxicity. It is known that molecules released from damaged muscle might act as 'danger' signals. These are known as 'alarmins', and contribute to the inflammatory reaction by activating the innate immune system. Here we show that the venoms of B. asper and C. d. terrificus release the mitochondrial markers mtDNA (from the matrix) and cytochrome c (Cyt c) from the intermembrane space, from ex vivo mouse tibialis anterior muscles. Cyt c was released to a similar extent by the two venoms whereas B. asper venom induced the release of higher amounts of mtDNA, thus reflecting hitherto some differences in their pathological action on muscle mitochondria. At variance, injection of these venoms in mice resulted in a different time-course of mtDNA release, with B. asper venom inducing an early onset increment in plasma levels and C. d. terrificus venom provoking a delayed release. We suggest that the release of mitochondrial 'alarmins' might contribute to the local and systemic inflammatory events characteristic of snakebite envenomations.